Faktor-faktor yang mempengaruhi wisatawan dalam pemilihan akomodasi di Kabupaten Jembaran - Ni Putu Krisnadevi; Anak Agung Putri Sri; Agus Muriawan Putra (Jurnal Kepariwisataan dan Hospitalitas, 2021)
Tourist accommodation is one of the supporting activities of tourism in Jembrana Regency. However, there are many accommodations that fail to operate due to the small number of tourist arrivals. The purpose of this study is to determine the factors that influence tourists choosing accommodation in Jembrana Regency and the dominant factors affecting tourists in choosing accommodation in Jembrana Regency so it can use as input for accommodation providers to manage tourist accommodation in Jembrana Regency. Methods of collecting data are through observation, questionaire, documentation and literature study method. Method for data analysis are use descriptive qualitative method through validity test, reliability test, and analysis factor using SPSS program version 22. The result of the study show that according to validity and reliability test done by SPSS version 22 all 21 indicators are valid and reliable that mean it can be continued to factor analysis. Based on the results of factor analysis, there are 4 factors consisting of 14 indicators that influence tourists in the selection of tourist accommodation in Jembrana Regency such as Service Quality Factors, Reputation Factors, Location Factors and Price Factors. The dominant factor influencing tourists in choosing accommodation in Jembrana Regency is the Service Quality Factor which is formed on 4 indicators, such as choosing accommodation due to the ability of staff to communicate well, choosing accommodation due to the completeness of room facilities, choosing accommodation based on the design of the accommodation building, choosing accommodation based on a friend or colleague’s reference